Implementasi Pembelajaran Daring dalam Mata Pelajaran Matematika Materi Pengukuran Sudut - Muhlis; Umi Isroul Mahmudah; Sukriadi (Jurnal Ilmu Pendidikan Dasar Indonesia, 2021)
This research is motivated by the mathematics learning of angle measurement material which is carried out online due to the covid-19 pandemic so that mathematics learning which should be studied intensively with face-to-face learning so that students more easily understand this material cannot be carried out due to the covid-19 pandemic which resulted in learning mathematics is not optimal. This study aims to determine the preparation of teachers in implementing online learning, to determine the implementation of online learning on angle measurement material, and to determine the supporting and inhibiting factors in applying online learning to angle measurement material in class IV SDN 007 Sungai Kunjang. The results showed that the teacher had carried out online learning of angle measurement material with good preparation. The application of online learning of angle measurement material went well with obstacles that the teacher could overcome. The supporting factors for online learning are devices and adequate internet quotas and the inhibiting factor for online learning is not having a device and internet quota. Based on the results of the research above, it can be concluded that teacher preparation in carrying out online learning plays a major role in achieving learning objectives and adequate learning facilities will make it easier for students to carry out online learning of this angle measurement material.